SAT0216 Chest Ultrasound Signs of Interstitial Lung Disease in Systemic Sclerosis Patients: A Comparison between High Resolution Chest Computed Tomography Findings. (15th July 2016) - Rotondo, C.; Chialà, A.; Nivuori, M.; Coladonato, L.; Giannini, M.; Anelli, M.G.; Righetti, G.; Scioscia, C.; Fiorentini, C.; Lopalco, G.; Lapadula, G.; Iannone, F.
Abstract : Background: Interstitial lung disease (ILD) is a typical clinical manifestation in Systemic Sclerosis (SSc). The high resolution chest computed tomography (HRCT) is the gold standard to evaluate and grade ILD. The presence of fibrotic tissue in the lung, or other structures beside the air, allows obtaining specific sonography images (such as ultrasound lung comet, higher pleural line thickness, irregular pleural margins and subpleural cysts) by chest ultrasound. In previous studies it was demonstrated that the ultrasound comets number increases in SSc patients. Objectives: We aimed at correlating the specific lung sonography signs with ground glass and honeycombing pattern detected by chest HRCT. Methods: A total of 60 SSc outpatients (54 female, mean age 56, 2 ± 13, 8 ys and disease duration of 9, 57±8, 7 ys), who fulfilled ACR/EULAR 2013 SSc classification criteria, were recruited. All patients underwent chest HRCT and US examination. The US examination was performed with 7, 5 Mhz probe and conducted with patients in sitting position from paraspinal line to anterior axillary line, for each intercostals space. The presence of typical ultrasound signs as lung comets (pathological if >35), higher pleural line thickness (pathological if >2mm), irregular pleural margins, subpleural cysts and pleural effusion was detected. The sensitivity, specificity and accuracy of US patterns (compared to chest HRTC) were evaluated by ROC analysis. Statistic significance was set at p<0.05. All results are expressed as mean ± 1 standard deviation. Results: 23 patients had the CT honeycombing pattern, of which 92% had the US irregular pleural margins, 70% had US higher pleural line thickness and sub-pleural cysts, just 54% had US lung comets. 16 patients had the CT ground glass pattern, of these in 94% the US irregular pleural margins, in 87% US lung comets, in 60% US higher pleural line thickness were found. As regard the CT ground glass pattern the US sign with the highest specificity (91%), sensibility (85, 7%) and accuracy (88%) was the lung comets; while regarding the CT honeycombing pattern the US sign with the highest specificity (92%), sensibility (69, 6%) and accuracy (82%). Conclusions: The lung US is a good diagnostic technique for its repeatability, low cost and risklessness. Although HRCT remains the best imaging technique to assess the ILD, in SSC the lung US could be a useful tool to detect the presence or the evolution of ILD and to improve the timing of HRTC without exposing the patients to high radiation doses over time. Disclosure of Interest: None declared